Vascular bed molecular profiling by differential systemic decellularization in vivo - Serra, Aida (2020)
Objective- Vascular endothelial dysfunction is a key component of several major human diseases, but the molecular basis of this complex disorder has been difficult to determine in vivo. Previous attempts to identify key mediators of vascular endothelial dysfunction in experimental models have been limited by the lack of suitable methods for system-wide analyses of vascular bed biology. Here, we aimed to develop a novel method for investigating vascular endothelial dysfunction pathogenesis that enables system-wide analyses of molecular interactions between endothelial glycocalyx, endothelial cells, and smooth muscle cells in murine. Approach and Results- We developed a new technique using whole-body differential perfusion with increasing concentrations of detergent buffer to selectively solubilize distinct layers of vascular bed tissue in rodents. When combined with proteomics techniques, our novel approach of differential systemic decellularization in vivo enabled quantitative profiling of vascular beds throughout the body. Initial perfusion with phosphate buffer was used to obtain the endothelial glycocalyx, followed by subsequent extraction of endothelial cell components, and finally by smooth muscle cell constituents with increasing concentrations of detergent. Differential systemic decellularization in vivo has also been successfully applied to characterize molecular events in the vascular bed pathology of lipopolysaccharide-challenged mice. Conclusions- Together, these data indicate that differential systemic decellularization in vivo permits system-wide molecular characterization of vascular bed proteomes in rodent models and can be used to advance our current understanding of vascular endothelial dysfunction pathogenesis and progression in a wide range of disease settings.